2021
DOI: 10.1016/j.bjid.2021.101595
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 assessment in an outpatient dialysis facility of a single center in Brazil

Abstract: Background The reported incidence and fatality rates of SARS-CoV-2 infection in patients receiving maintenance dialysis are higher than those of the general population. Objective This study sought to characterize the clinical characteristics and outcomes following COVID-19 infection in this population in a single center in Brazil. Methods Out of 497 dialysis patients evaluated between March 1 st , 2020 and February … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 19 publications
1
11
0
7
Order By: Relevance
“…Other studies also found a higher COVID-19 fatality rate in the PD group than in the HD group (33% vs. 29.6% 22 and 45.6% vs. 34.5% 23 ), corroborating our previous study that showed that the PD group had a higher rate of severe COVID-19 than the HD group. 8 In contrast, Weinhandl et al reported that the PD group had a much lower risk of hospitalization than the HD group 27 . Hsu et al did not find significant differences in the morbidity and mortality rates between the HD and PD groups with COVID-19 2 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Other studies also found a higher COVID-19 fatality rate in the PD group than in the HD group (33% vs. 29.6% 22 and 45.6% vs. 34.5% 23 ), corroborating our previous study that showed that the PD group had a higher rate of severe COVID-19 than the HD group. 8 In contrast, Weinhandl et al reported that the PD group had a much lower risk of hospitalization than the HD group 27 . Hsu et al did not find significant differences in the morbidity and mortality rates between the HD and PD groups with COVID-19 2 .…”
Section: Discussionmentioning
confidence: 96%
“…24 Moreover, telehealth has played a pivotal role in the current pandemic and should be implemented whenever possible; however, the quality of evidence is controversial. [25][26] Studies evaluating the impact of COVID-19 on PD and HD patients have conflicting results 2,8,22,23,27 . Our study found higher hospitalization, oxygen therapy need, mechanical ventilation, mortality, and fatality rates (52.9% vs. 19.4%; p = 0.005) in the PD group than in the HD group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En la literatura existen muy pocos trabajos que evalúen especí camente las alteraciones del gusto u olfacción por COVID-19 en la población en diálisis. El trabajo de Polacchini et al en Brasil reportó una prevalencia alta (47,7 %) de alteración del gusto o la olfacción en 44 pacientes que presentaron COVID-19, esta prevalencia fue similar en los casos leves, moderados y severos [7], sin embargo, no se menciona si las alteraciones precedieron, fueron concomitantes o posteriores a la aparición de los síntomas clásicos o si fue el único síntoma de COVID-19. Feehan et al realizaron un trabajo de prevalencia para indagar sobre la importancia de la anosmia o la ageusia en casos asintomáticos y sintomáticos de COVID-19; encontraron en su población un 4,8 % de pacientes con anosmia o ageusia, la cual aumentó a 29,9 % en los pacientes con rmados de COVID-19; la prevalencia del factor (síntoma presente en casos positivos divididos por el total de reportes) fue del 40,6 % [8].…”
Section: Discussionunclassified
“…Como una unidad renal es un sitio potencial de mayor prevalencia de COVID-19, con las implicaciones que tienen, como una alta tasa de hospitalización y muerte como la reportada por Polacchini et al [7] en Brasil, estos mismos argumentos nos motivaron a la realización del presente estudio; sin embargo, solo encontramos un número bajo de pacientes con COVID-19 y alteraciones de la olfacción que pudo explicarse por estar en ese momento en Colombia en una etapa posprimera ola de COVID-19. A pesar de lo anterior, nuestros resultados aportan datos importantes en la población en diálisis no reportados previamente.…”
Section: Discussionunclassified